Forensic medical evaluation of non-fatal occupational accidents: the case of Eskişehir - Şimşek, Ümit; Kılıboz, Tuğrul; Karbeyaz, Kenan (The Bulletin of Legal Medicine, 2025)
Objective: Occupational accidents are forensic cases that represent a significant public health issue across all countries. This study retrospectively evaluated non-fatal occupational injury cases referred to our forensic medicine clinic for trauma-related assessment. The aim was to share the demographic and incident-related characteristics of these cases in light of the existing literature.  Method: The cases of non-fatal occupational accidents admitted to Eskişehir Osmangazi University Faculty of Medicine, Department of Forensic Medicine between the years 2019-2024 were evaluated retrospectively. Demographic data, injury types, injury severity and forensic report contents of the cases were evaluated. The data were uploaded to SPSS programme and evaluated. Frequency, standard deviation, median, mode, minimum and maximum values were used and chi-square test was applied. Statistical significance was accepted as p
Keywords: Forensic medicine; Forensic report; Clinical forensic medicine; Trauma scoring; Occupational accident